2022
DOI: 10.3390/curroncol29080464
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Survival Outcomes of Patients following the Harrington Procedure for Complex Acetabular Metastatic Lesions

Abstract: Background: The Harrington surgical technique makes it possible to manage complex, extensive bone lesions using pins and cement to consolidate bone for acetabular cup positioning. However, it may be associated with a high reoperation rate, and the functional results of this surgery are not precisely described in the literature. Methods: In a monocentric retrospective study including all patients operated on using the Harrington procedure associated with THA between 2005 and 2020, we aimed to assess preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Without the help of the TINAVI robot, surgeons spend more time locating the surgical site, multiple rounds of radiation are required, and most parts of the final positioning are not as precise as when using the TINAVI robot. When comparing the clinical outcomes with the other surgical methods in the treatment of acetabular metastasis reported by Yang et al (2020), Lavignac et al (2020), Houdek et al (2020), and Plaud et al (2022, our treatment has the shortest surgical time (45 ± 10) and has minimal intraoperative blood loss (42 ± 8.37). None of the complications reported by others have appeared in our research so far (Table 3).…”
Section: Figurementioning
confidence: 90%
See 1 more Smart Citation
“…Without the help of the TINAVI robot, surgeons spend more time locating the surgical site, multiple rounds of radiation are required, and most parts of the final positioning are not as precise as when using the TINAVI robot. When comparing the clinical outcomes with the other surgical methods in the treatment of acetabular metastasis reported by Yang et al (2020), Lavignac et al (2020), Houdek et al (2020), and Plaud et al (2022, our treatment has the shortest surgical time (45 ± 10) and has minimal intraoperative blood loss (42 ± 8.37). None of the complications reported by others have appeared in our research so far (Table 3).…”
Section: Figurementioning
confidence: 90%
“…Frontiers in Bioengineering and Biotechnology frontiersin.org higher than in young patients, as confirmed by studies that have shown that the main complications are pin migration and infection in acetabular metastasis patients who undergo open surgery (Houdek et al, 2020;Lavignac et al, 2020;Plaud et al, 2022). Therefore, open surgery may not be suitable for treating acetabular metastasis patients who are elderly and with multiple diseases.…”
Section: Figurementioning
confidence: 99%
“…Periarticular metastatic damage often causes gradual displacement of the femoral head towards the top and inner side of the acetabulum, sometimes resulting in acute acetabular fractures or collapse; despite effective radiotherapy, this site may experience local bone dissolution and necrosis, leading to pathological fractures or joint collapse [14]. In these critical situations, surgical treatment is necessary, and hip joint surgery itself is complex [15]. The most used classi cation system for periacetabular bone metastases is the Harrington classi cation [16].…”
Section: Introductionmentioning
confidence: 99%